2007
DOI: 10.1080/08880010701198787
|View full text |Cite
|
Sign up to set email alerts
|

Biphenotypic Extramedullary Blast Crisis as a Presenting Manifestation of Philadelphia Chromosome-Positive CML in a Child

Abstract: A 14-year-old child presented with generalized lymphadenopathy and massive hepatosplenomegaly. Peripheral smear and bone marrow examination were suggestive of Ph' positive chronic myeloid leukemia (CML) in chronic phase. However, lymph node biopsy showed extramedullary blast crisis with evidence of myeloid and T cell markers in blasts. Reverse transcriptase-polymerase chain reaction from lymph node aspirate revealed transcript for bcr-abl p210. Thus, we present here a unique case of childhood CML with extramed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Literature review shows few rare case reports too in which immunohistochemistry of extra medullary granulocytic sarcoma had shown T cell lineage extra medullary blast crisis [2,[10][11][12][13]. Extra medullary blast crisis with biphenotypic picture (mixed myeloid and T cell features) were also reported separately by Hossain et al [14],Cervantes et al [15], Ganessan et al [16] and Chen et al [17].…”
Section: Discussionmentioning
confidence: 99%
“…Literature review shows few rare case reports too in which immunohistochemistry of extra medullary granulocytic sarcoma had shown T cell lineage extra medullary blast crisis [2,[10][11][12][13]. Extra medullary blast crisis with biphenotypic picture (mixed myeloid and T cell features) were also reported separately by Hossain et al [14],Cervantes et al [15], Ganessan et al [16] and Chen et al [17].…”
Section: Discussionmentioning
confidence: 99%
“…5 An extramedullary blast crisis at presentation is even rarer with this phenomenon being cited in individual case reports. 6 Various signs and symptoms may occur as a result of the specific effect of an extramedullary blastic tumor. In this current case, the tumor involved the leptomeninges and the patient developed neurologic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…It took a rather long time for most cases to develop extramedullary blast crisis after their initial diagnoses [4,10,11,12,13,14]. Only 2 cases were diagnosed with blast crisis at the initial presentation [15,16]. In addition, Kim [17] described 2 cases of sudden extramedullary T lymphoblastic blast crisis, and it was suggested that the cessation of imatinib may have contributed to this phenomenon.…”
Section: Discussionmentioning
confidence: 99%